THE CORRELATION BETWEEN PERCEIVED CRITICAL THINKING AND READING COMPREHENSION ABILITY - Nugrahanto, Pungky Tri; Nurkamilah, Nurkamilah; Oktarini, Widya (Jurnal Pendidikan Bahasa Inggris Proficiency, 2023)
This study aims to find out students’ critical thinking skill, students’ reading comprehension ability, and the correlation between students’ critical thinking and reading comprehension ability. Data were collected from 90 students from the 7th grade of SMPN 1 Ajung, selected from three different classes. The researcher used a questionnaire from Mincemoyer and Perkins (2005) to measure the students’ critical thinking and taking the reading comprehension score from the help of the classroom teacher. The data were analyzed using descriptive statistic and Pearson Product Moment in SPSS 19. Pearson Product Moment was used to find the correlation between students’ critical thinking and reading comprehension ability. The findings showed that students’ critical thinking skill was in the middle level (52-67) and students’ score in reading comprehension was in the good level (61-85). The finding shows that the Pearson Correlation Coefficient between variable students’ critical thinking and variable students’ reading comprehension is (r = 0.542). Which means the correlation between the two variables is moderate. Statistically, there is a correlation between critical thinking and reading comprehension of the seventh-grade students of SMPN 1 Ajung. Overall, this finding has implications for educators who may want to consider incorporating critical thinking skills into reading comprehension instruction to improve students' performance in this area. It also highlights the need for further research to investigate the relationship between perceived critical thinking and reading comprehension in other populations and contexts.